2020
DOI: 10.15376/biores.15.3.4802-4822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaCO3 on the wood properties of tropical hardwood species from fast-growth plantation in Costa Rica

Abstract: This work aimed to evaluate the effect of the precipitation of CaCO3 via subsequential in-situ mineral formation based on a solution-exchange process of two solution-exchange cycles via impregnation with CaCl2 in ethanol and NaHCO3 in water. The effects were investigated in terms of the structure of the wood and the thermal, physical, mechanical, and decay resistance properties of nine species commonly used in commercial reforestation in Costa Rica. The thermogravimetric analysis results showed that the woods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 6 publications
3
17
0
Order By: Relevance
“…The TGA results showed that the mineralized samples degraded faster at the beginning of the test, but after 350 • C, this behavior reversed, and finally the untreated samples were more extensively degraded. These results are in agreement with those reported previously in the literature for different CaCO 3 -treated samples [15,23]. It has been proposed that a fast initial degradation of CaCO 3 -treated wood samples was due to the early degradation of CaCO 3 , H 2 O, and CO 2 [24] before reaching 100 • C (Figure 5).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The TGA results showed that the mineralized samples degraded faster at the beginning of the test, but after 350 • C, this behavior reversed, and finally the untreated samples were more extensively degraded. These results are in agreement with those reported previously in the literature for different CaCO 3 -treated samples [15,23]. It has been proposed that a fast initial degradation of CaCO 3 -treated wood samples was due to the early degradation of CaCO 3 , H 2 O, and CO 2 [24] before reaching 100 • C (Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…The mineralization of wood with CaCO 3 has been proposed by several authors to increase wood's fire resistance, but to our knowledge, a method comprising sequential gas diffusion has not been reported. Most of the reported treatments use liquid diffusion of CaCl 2 in combination with a number of agents, such as sodium hydroxide and supercritical carbon dioxide [23], aqueous sodium carbonate with dodecanoic acid [11], sodium bicarbonate [14,15,27], ammonium carbonate [28], sodium carbonate, alkaline hydrolysis of dimethyl carbonate [17], and calcium dimethylcarbonate in methanol [13]. In addition, a novel method was recently proposed consisting in impregnating wood with calcium acetoacetate [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, mineralisation increased water uptake in the submersion test, while thermal modi cation had the opposite effect (Table 1). An increased water uptake in submersion tests following mineralisation with CaCO 3 was also reported by Moya et al (2020), while crystals in the wood were previously seen to have a similar effect on sorption properties in wood treated with NaCl and H 3 BO 3 (Lesar et al 2011). In mineralised thermally modi ed wood, the thermal modi cation somehow neutralises the effect of mineralisation.…”
Section: Resultssupporting
confidence: 59%
“…As mentioned previously, mineral species (e.g., CaCO 3 and BaSO 4 ) can be used to modify the structural properties and thermal degradation behavior of biomass. ,, However, in this case, the biomass structure is impregnated to the core using soluble metal salt that diffuses deeply inside the wood porosity and cell walls, leading to in situ formation of the desired mineral species. In the present study, the objective was to emulate a painted/varnished wood by coating the wood chips with the mineral components of paints and vanish, using water suspensions of TiO 2 , CaCO 3 , and BaSO 4 powders.…”
Section: Resultsmentioning
confidence: 99%